2022
DOI: 10.12659/msm.936397
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Rehabilitation Program on the Change in Components of Body Mass of the Upper and Lower Limbs in People After Ischemic Stroke

Abstract: Background The aim of this study was to evaluate the effects of rehabilitation in terms of changes in the body mass composition in the upper and lower limbs depending on the length of time after stroke and the age of the patient. Material/Methods Eighty-two patients after ischemic stroke were tested 3 times: on admission, after 5 weeks, and 3 months after leaving the hospital (follow-up). During each examination, a segmental analysis of the components of the body mass o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…2 However, once survivors miss the opportunity of revascularization within 24 hours after the initial stroke, they must rely on spontaneous or rehabilitation-supported functional recovery. 3,4 It is reported that almost half of IS patients have lifelong disabilities, 5 and survivors with motor cortex involvement and descending motor fiber damage had shown motor deficits, especially the impairment of hand dexterity, severely affecting their quality of life. 6 To date, neurological deficits in IS patients remain incurable due to the limited regeneration capacity in the central nervous system (CNS).…”
Section: Introductionmentioning
confidence: 99%
“…2 However, once survivors miss the opportunity of revascularization within 24 hours after the initial stroke, they must rely on spontaneous or rehabilitation-supported functional recovery. 3,4 It is reported that almost half of IS patients have lifelong disabilities, 5 and survivors with motor cortex involvement and descending motor fiber damage had shown motor deficits, especially the impairment of hand dexterity, severely affecting their quality of life. 6 To date, neurological deficits in IS patients remain incurable due to the limited regeneration capacity in the central nervous system (CNS).…”
Section: Introductionmentioning
confidence: 99%
“…This postural instability not only compromises the ability to maintain balance while standing, but also impairs the capacity to regain balance in the face of external destabilizing stimuli 6 . Consequently, individuals with compromised balance face a heightened risk of falling, leading to both economic burdens and social ramifications 7,8 . Given these challenges, stroke rehabilitation primarily focuses on enhancing fall prevention strategies, improving balance, and gait patterns 9,10 …”
Section: Introductionmentioning
confidence: 99%
“…6 Consequently, individuals with compromised balance face a heightened risk of falling, leading to both economic burdens and social ramifications. 7,8 Given these challenges, stroke rehabilitation primarily focuses on enhancing fall prevention strategies, improving balance, and gait patterns. 9,10 Effective postural stability is crucial for performing routine activities, and attentional cognitive processes play a key role in maintaining a stable posture.…”
Section: Introductionmentioning
confidence: 99%